2000
DOI: 10.1046/j.1440-1703.2000.00330.x
|View full text |Cite
|
Sign up to set email alerts
|

Seed dispersal and predation by Yakushima macaques, Macaca fuscata yakui, in a warm temperate forest of Yakushima Island, southern Japan

Abstract: The relationships between fruit morphology and the foraging behavior of the Yakushima macaque, Macaca fuscata yakui were studied during a 9‐month field study and series of laboratory experiments on Yakushima Island, southern Japan. These relationships may affect seed germination traits through seed dispersal. The macaques’ foraging behavior was observed in order to obtain data concerning the treatment of pulp and seeds. Seeds in feces and spat seeds were collected and analyzed. A linear discriminant analysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 40 publications
(57 reference statements)
1
44
1
Order By: Relevance
“…in both study areas, in particular P. ssiori and P. grayana, were approximately 5 mm in diameter (Nakayama et al 2000). The maximum size of seeds studied (4.1 mm or approximately 5 mm) was smaller than that swallowed and dispersed in Yakushima Island (6.35 mm, Elaeocarpus japonicus; Otani and Shibata 2000), implying that the macaque swallowed these seeds leaving some margins.…”
Section: Resultsmentioning
confidence: 78%
“…in both study areas, in particular P. ssiori and P. grayana, were approximately 5 mm in diameter (Nakayama et al 2000). The maximum size of seeds studied (4.1 mm or approximately 5 mm) was smaller than that swallowed and dispersed in Yakushima Island (6.35 mm, Elaeocarpus japonicus; Otani and Shibata 2000), implying that the macaque swallowed these seeds leaving some margins.…”
Section: Resultsmentioning
confidence: 78%
“…The explanation is probably different for each species, because among a variety of dispersal systems, animal, wind, and/or gravitydispersed species show different fecundities, dispersal distances, and clumping. Because 12 out of 17 species were animal-dispersed, seeds of these species should have been dispersed far from the mother trees by frugivorous birds and/or monkeys in this area (Noma and Yumoto 1997;Yumoto et al 1998;Otani and Shibata 2000). Seeds of these species were dispersed in a wider and more even fashion among topographic positions than trees of the adult stages (Fig.…”
Section: Aggregated Distribution At Each Life Stagementioning
confidence: 97%
“…Bedd., had capsules, and their seeds were dispersed by gravity and wind. Seeds of T. gymnanthera are also thought to be dispersed by the Japanese macaque Macaca fuscata yakui and birds (Noma and Yumoto 1997;Yumoto et al 1998;Otani and Shibata 2000).…”
Section: Distribution Patternsmentioning
confidence: 99%
“…Further, ingestion by macaques enhanced germination for seeds of several plant species [Otani & Shibata, 2000], although many seeds were masticated before ingestion [Otani, 2004;Tsuji et al, 2010b]. A recent study found that the topography of dispersed seeds matched the distribution of trees of target plants, which implies that the macaques contribute to the colonization and expansion of plant populations [Tsujino & Yumoto, 2009].…”
Section: Introductionmentioning
confidence: 99%
“…Japanese macaques primarily feed on fleshy fruits and nuts throughout their range, especially in fall (September-November; reviewed in Tsuji, 2010, Tsuji et al, 2015, and defecate and spit out seeds of 12-35 plant species [Otani & Shibata, 2000;Tsuji, 2011Tsuji, , 2014Tsuji et al, 2011] inside forests. Further, ingestion by macaques enhanced germination for seeds of several plant species [Otani & Shibata, 2000], although many seeds were masticated before ingestion [Otani, 2004;Tsuji et al, 2010b].…”
Section: Introductionmentioning
confidence: 99%